Performance Evaluation of a Standalone OFDM System for Digital Image Transmission over AWGN Channels - Ade silvia handayani; Sarjana; Aryanti; Nurhajar Anugraha; Muhammad Hanif Fatin; Devi Wahyuni; Muhammad Rafly Wijaya; Dely Andini (Politeknik Negeri Cilacap, 2026)
This study investigates the performance of a standalone digital communication system based on Orthogonal Frequency Division Multiplexing (OFDM) for digital image transmission over Additive White Gaussian Noise (AWGN) channels. The system was tested using two digital modulation techniques: Binary Phase Shift Keying (BPSK) and Quadrature Phase Shift Keying (QPSK). Unlike previous studies that focused on OFDM implementation in large-scale communication systems such as cellular networks, this research explores a simplified standalone scenario without any supporting network infrastructure. Simulations were carried out in the MATLAB environment using grayscale image inputs ranging from 1 MB to 10 MB, with signal-to-noise ratio (SNR) levels varying from 0 to 30 dB. The results show that BPSK modulation maintains a low Bit Error Rate (BER) of approximately 0.077 even under low SNR conditions (as low as 0 dB). In contrast, QPSK modulation achieves optimal performance when the SNR reaches at least 15 dB, where the BER drops to 0.00000. The image size did not significantly affect system performance, indicating robustness across varying data loads. Overall, the findings suggest that BPSK provides higher reliability in noisy channels, whereas QPSK offers better spectral efficiency under cleaner conditions. Therefore, the proposed standalone OFDM system demonstrates strong potential for lightweight data communication applications such as sensor networks and remote monitoring systems operating in limited network environments.